Infiltration of Appendix with Eosinophils in Acute Appendicitis: A Prospective Study - Swati Patel; Himanshu Soni; Vishwadeep Kesarwani; S Nandedkar; M Purohit (Tropical Journal of Pathology and Microbiology, 2021)
Background and Aim: Acute eosinophilic appendicitis is an uncommon ammatory condition of appendix. The histological hallmark of the entity is eosinophilic in rather than neutrophilic, of the muscularis propria with accompanying edema, separating muscle. The aim of the present study was to study the etiology and prevalence of eosinophilic appendicitis. Material and Methods: The tissue specimens were included from the appendectomy procedure done either as elective or emergency procedure in the surgical department of the hospital. Total of 125 cases where studied for the period of one year. The related clinical history and the data of the patients were obtained from the surgical department of the hospital. The tissue samples of the studied cases were processed in the department of pathology. For light microscopy one slide from each block was stained with H&E to arrive at a diagnosis. Results: In 125 cases of appendectomies were studied out of which 73 cases (59%) of the appendectomies were performed as an emergency procedure and 52 cases (41%) were done as an elective procedure. Out of 125 cases, 118 cases (95%) of the appendectomy specimens showed congested and dilated blood vessels on the external surface, 121 cases (97%) of appendectomy were send along with mesoappendix which also showed signs of congestion. The major cause of appendectomies performed was for acute appendicitis 72 cases (58%) followed by periappendicitis 17 cases (13.2%).In the cases of acute appendicitis and periappendicitis, also a male predominance was seen, which was 72 cases(57.6%) and 9 cases (55%). Conclusion: The etiology of appendicitis is multifactorial: obstruction, diet and infection. Inflammation triggered by type 1 hypersensitivity allergic response is a recently described etiology. Acute eosinophilic appendicitis shares similar morphological features as acute appendicitis with a male predominance. It is most commonly seen between the age group of 20-30 years of age. Histopathologic features of acute eosinophilic appendicitis include absence of neutrophils,